Black pigmented bacteria in the wall of the periodontal pocket at the beginning and end of the periodontal therapy - Maita Véliz, Luis (2016)
Objective: Determine the presence of black pigmented bacteria (BNP) in periodontal pockets before and after periodontal treatment. Materials and method: The type of study is descriptive which has a sample of 10 areas, ten patients in which periodontal pockets were identified, samples were taken with paper cones, which were then cultured in blood agar medium with hemin and vitamin K, incubated. Subsequently he identified and counted the black pigmented colonies before and after periodontal treatment. Results: Of the first samples examined before treatment could be recovered BNP 60 % of cultured samples with a range of presence of 16-312 CFU and samples obtained after periodontal treat-ment could be recovered in 50 % of them , with a range of 5 to 70 presence UFC, and this is confirmed by statistical analysis. Conclusions: It is concluded that BNP is present in periodontal pockets and that they reduce their presence, after periodontal therapy.